The effectiveness of Frsc public education programme on drivers' road traffic habit in Lagos and Oyo state of Nigeria (2012)
This study assessed the effectiveness of the Federal Road Safty Commission public education programme in improving drivers' habit/behaviour on Nigerian road and highways. Multi-stage sampling technique was used in selecting subjects, which consist of 210 commercial vehicle drivers. Two instruments developed and validated by the researcher were administered on the drivers. Cronbach Alpha and Scot-pie formula were used to compute the reliability coefficients of the instruments were determined using factor analysis. Data collected were analysed using factor analysis. Data collected were analysed using percentages, t-test and ANOVA. Some of the research questions were tested at 0.05 level of significance. The result showed that the programme has imporved commercial vehicle drivers' habit/behaviour on roads and also, that there was significant difference in the road traffic behaviour of drivers based on state basis (t=9.99, df,208). The study equally revealed a significant difference in the behaviour of drivers based on driving experience (F4,205 p<0.05=2.795). It was therefore recommended that the Federal road safety commission should intesify their efforts in enlightenment campaign in order to inculcate good traffic culture in drivers with regard to the laws guiding road usage as well as enforce the traffic rules without fear or favour